Анатомічні особливості будови листкової пластинки видів роду Begonia L. (Begoniaceae C. Agardh) - Belaeva, Ya.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2015)
The aim – to study anatomical structure of leaf blade of the genus Begonia L. species and its connection with the peculiarities of habitats in which plants occur in nature. Material and Methods. The study was conducted with 8 species of the genus Begonia, which grow in the glasshouses of the M.M. Gryshko National Botanical Garden of the NAS of Ukraine. Normally developed leaves of the middle formation were taken as samples. In order to make photos of epidermal and mesophyll cells slices and biometric researches light microscope equipped with a digital camera was used. Measurements were performed using licensed programs Axio Vision Rel. 4.7 (Carl Zeiss, Jena, Germany). Results. The most mesophyllous species are B. dichotoma and B. dregei, the least mesophyllous – B. mollicaulis and B. venosa. Only in B. subvillosa prevalence of palisade parenchyma was found. In contrast to all other studied species, B. subvillosa grows in open areas. In other species domination of spongy parenchyma was established. The presence of hypoderm in B. venosa leaf blade and large epidermal cells in other model species is an adaptation to adverse conditions especially the lack of moisture. Conclusions. Prevalence of spongy parenchyma in leaf blades of studied species indicates “shadow” mesophyll structure that allows them to grow in terms of shading. Xeromorphic adaptations of the genus Begonia species include the presence of large elongated epidermal cells and hypoderm. An important role in reducing the evaporation intensity from the leaf surface plays cuticle and trichomes.